Community commitment to manage forests that integrate al-'urf values in reducing tenurial conflicts from an islamic legal perspective - Hamka, Hamka; Satriani, Indra; Raziq, Abd.; Atika, Nur; Eril, Eril; Wulandari, Natasya; Harmilawati, Harmilawati (Asy-Syari’ah : Jurnal Hukum Islam, 2025)
This research examines the community's commitment to managing forests by integrating al-'Urf values to reduce tenure conflicts among forest area communities. This research contributes to discussions regarding forest conservation from an Islamic law perspective. This research is a qualitative study using observation, interviews and documentation methods in collecting data, namely going directly to the field which is the object of research. This research shows that it is important to have community commitment in managing forests by integrating al-'urf values. The local community's perception of forests is different from that of the government, where the government bases its designation on references to legislation that they themselves have made in the past. Community commitment in managing forests using the al-'urf approach plays an important role in reducing conflict and resolving or opening management and ownership rights to land or forests. Islamic law in this context focuses on forest management efforts based on the Koran, hadith and expert opinions in order to achieve the common interests and welfare of the community of all parties involved, whether local, government or other parties with an interest in forest preservation. Community efforts to reduce tenure conflicts through Islamic Law with the 'urf approach can resolve land disputes that are not only based on individual or group rights, but also consider the long-term impact on shared prosperity that prioritizes the principles of justice, sustainability and social harmony, with the aim of achieving a solution that benefits all parties without harming any party.